Soil ecology - Killham, Ken (Cambridge University Press, 1994)
The book emphasizes the interrelations among plants, animals, and microbes, by first establishing the fundamental physical and chemical properties of the soil habitat and then functionally characterizing the major components of the soil biota and some of their most important interactions. The fundamental principles underpinning soil ecology are established and this then enables an integrated approach to explore and understand the processes of soil nutrient (carbon, nitrogen, and phosphorus) cycling and the ecology of extreme soil conditions such as soil-water stress. The book selects two of the most topical aspects of applied soil ecology : the ecology of soil pollution is examined, focusing on acid deposition and radionuclide pollution ; manipulation of soil ecology through biotechnology is discussed, illustrating the use of pesticides and microbial inocula in soils and pointing toward the future by considering the impact of genetically modified inocula on soil ecology